(untitled) (Orfeu, 2020)
The paper discusses the composition process of four pieces by the author, using the notions of ‘musical material’ and ‘model’. A model would be a combination of formal features that are extracted from a musical material to project itself in another context. The models involve principles of organizations that apply to different aspects of the formal dimension of music. Several excerpts from the author’s pieces are analyzed based on the same notions. The use of computational modeling (CAC) in the composition process is also discussed.